2021
DOI: 10.1021/acsomega.1c04187
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Breaker Systems To Remove Residual Polymer Damage in Hydraulically Fractured Reservoirs

Abstract: Hydraulic fracturing is a widely used technology to enhance the productivity of low-permeability reservoirs. Fracturing fluids using guar as the rheology builder leaves aside residual polymer layers over the fractured surface, resulting in a restricted matrix to fracture flow, causing reduced well productivity and injectivity. This research developed a specialized enzyme breaker and evaluated its efficiency in breaking linear and cross-linked guar-polymer gel as a function of time, temperature, and breaker con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Mannanase-II has been reported to remain active in the range of 40−70 °C. 155 Ghosh et al 156 developed a thermally activated enzyme breaker with a temperature resistance of 120 °C, whose main ingredient is galactomannanase, which was able to degrade 94−98% of the filter cake formed by cross-linking HPG guar with sodium tetraborate at 120 °C in only 6 h. They compared the effect of this enzyme with several acid gel-breaking agents such as chlorous acid, sodium bromate, and diammonium peroxidisulfate. At 148.8 °C, the breaking time of the enzyme was longer, taking 24 h, but it produced the least amount of residue.…”
Section: Other Additivesmentioning
confidence: 99%
“…Mannanase-II has been reported to remain active in the range of 40−70 °C. 155 Ghosh et al 156 developed a thermally activated enzyme breaker with a temperature resistance of 120 °C, whose main ingredient is galactomannanase, which was able to degrade 94−98% of the filter cake formed by cross-linking HPG guar with sodium tetraborate at 120 °C in only 6 h. They compared the effect of this enzyme with several acid gel-breaking agents such as chlorous acid, sodium bromate, and diammonium peroxidisulfate. At 148.8 °C, the breaking time of the enzyme was longer, taking 24 h, but it produced the least amount of residue.…”
Section: Other Additivesmentioning
confidence: 99%
“…Abdelrahim et al revealed the residual damage mechanism of fracturing fluid. 64 The main problem is the intrusion of polymers into pore throats, increasing the level of binding water between rock pores and the surface of proppants. In addition, due to the adsorption of fluids, the matrix expands and the pore space decreases, resulting in a decrease in fracture conductivity.…”
Section: Application Advantages For Ves Fracturing Fluidsmentioning
confidence: 99%
“…69 The MAS-1 polymer synthesized by Zhang et al was used in core-damage experiments, and the results showed that the permeability damage rate was between 12.64%−17.62%. 70 Ghosh et al 64 used the enzyme breaker developed to break the cross-linked HPG fluid and regained the matrix fracture permeability to 80%−95%. The retained permeability of the metal-cross-linked synthetic polymer fluid tested by Lee et al with a temperature resistance of up to 232 °C is less than 80%.…”
Section: Application Advantages For Ves Fracturing Fluidsmentioning
confidence: 99%
See 2 more Smart Citations